Pelatihan Pengolahan Singkong menjadi Keripik bagi Pemuda untuk Meningkatkan Kreatifitas di Masa Covid-19 di Desa Sukadana - Terasne Terasne; Tri Setianingsih; Ahmad Hanan; Sri Sukarni; Baiq Zuhrotun Nafisah (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
This Community Service Activity (PKM) aimed to improve skill (creativity) and increase the knowledge of Sukadana village youth to be more creative in their activities even at home during the Covid-19 period and create opportunities to become new entrepreneurs based on cassava processing of the Sukadana village community for youth and surrounding communities namely teachers and students through training in processing cassava into "Chips" or called ” “Keripik” which have high economic value and can be sold in the market. The methods used in PKM activities are socialization, counseling, training and mentoring. While the activity procedures are, socialization and preparation of activities, intensive training on processing cassava products into chips, monitoring and evaluation (activity response and product feasibility testing), and product marketing. The result of this activity is the processed product of "Chips" in Sukadana village. The results of PKM activities generally include several components as follows: 1) The success of meeting the target number of training participants, 2) The achievement of training objectives, 3) The achievement of the planned material targets, 4) The ability of participants in mastering the material. The achievement of the training objectives in general was very smooth and good, all materials could be delivered in detail. The results of the training of the participants that the quality of the chips that have been produced has met the savory taste, it can be concluded that the purpose of this activity has been well achieved.